HIGH-PRESSURE VEINS IN ECLOGITE FROM NEW CALEDONIA AND THEIR SIGNIFICANCE FOR FLUID MIGRATION IN SUBDUCTION ZONES - Spandler C.; Hermann J. (My University, 2006)
This paper describes the petrology and geochemistry of high-pressure veins and associated metasomatic selvages that are hosted by eclogite in the Pouébo Eclogite Melange of northern New Caledonia. Isotopic and geochemical evidence indicates that the mafic host rock represents seafloor-altered fractionated MORB that underwent eclogite-facies metamorphism in a subduction zone. Within the host rock are cm-thick garnet-quartz-phengite veins that are enveloped by garnet-poor, omphacite-rich selvages or bleach zones. Petrography, thermometry, oxygen isotope characteristics, and mass balance calculations are used to show that the veins largely formed by fluid-mediated mass transfer from the bleach zones during prograde metamorphism. Minerals in the veins are free of inclusions, but the vein garnets preserve complex chemical zoning features that are not present in the host rock garnets. Vein garnets have Mn and HREE zoning patterns that are indicative of progressive garnet growth during prograde metamorphism, whereas Mg and Ca contents reveal prominent sector zoning and fine-scale intergrowth features. We propose that the veins formed over a prolonged period during subduction by local circulation of fluid that was sourced from prograde dehydration of minerals in the host rock. Fluid circulation may have been driven by episodic microcracking/sealing around garnet porphyroblasts, which led to significant mass transfer and progressive vein growth. Mass balance calculations and phengite trace element compositions also require the additional of pelite-derived components to the veins. These components were probably introduced into the veins at conditions close to peak metamorphism via a relatively small external fluid flux. This model for vein formation is consistent with previous studies that suggest fluid flow in deeply subducted oceanic crust is highly restricted in many cases. The delay of fluid migration after hydrous mineral breakdown may provide an important source of water for arc magmas as free fluid is transported to deeper levels in subduction zones. © 2006 Elsevier B.V. All rights reserved.
Keywords: ECLOGITE; FLUID FLOW; NEW CALEDONIA; SUBDUCTION; VEINS